White OLEDs: Color in the Corners: ITO‐Free White OLEDs with Angular Color Stability (Adv. Mater. 29/2013). (1st August 2013) - Gaynor, Whitney; Hofmann, Simone; Christoforo, M. Greyson; Sachse, Christoph; Mehra, Saahil; Salleo, Alberto; McGehee, Michael D.; Gather, Malte C.; Lüssem, Björn; Müller‐Meskamp, Lars; Peumans, Peter; Leo, Karl
<x xml:space="preserve">Abstract</x> High‐efficiency white organic light‐emitting diodes (OLEDs) are fabricated by Whitney Gaynor and co‐workers (see page 4006), using transparent electrodes composed of silver nanowires embedded in a transparent polymer. In addition to having a performance suitable for large‐area devices, these solution‐processed electrodes scatter light to enhance the Lambertian emission profile of the OLEDs as well as stabilize the emission color over all viewing angles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>